Learning path : Unity : easy game development with Unity 5. - Lavieri, Edward D., Jr.; Thorn, Alan; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2017)
"Unity is an exciting and popular engine in the game industry. Unity will ease your way of creating highly-optimized and beautiful 2D and 3D games by speeding up your development process. This Learning Path takes a practical, project-based approach to teach you game development with Unity 5. You will begin with setting the game project workflow. Then, you will learn scripting and creating user interface. Also, you will learn working with textures. Further, you will develop your Unity skills by exploring level design and animation. Next, you will learn to create and import assets and packages which you can add to your game. Also, you will be familiar with organizing game resources and optimizing game performance. Finally, you will learn debugging and testing game. By the end of this Learning Path, you will have developed an advanced knowledge of Unity and its powerful feature-set and will be able to create interactive, feature-rich, and highly optimized games with Unity 5."--Resource description page.
Unity 5 : creating the game environment / Edward Lavieri -- Unity 5 level design, lighting, and animation / Alan Thorn -- Unity 5 game development : Gameplay / Edward Lavieri.
Presenters, Edward Lavieri, Alan Thorn.
Title and publication information from resource description page (Safari, viewed July 11, 2017).
Keywords: Unity (Electronic resource); Computer games -- Development; Computer games -- Programming; Computer animation; Electronic books